2003
DOI: 10.1002/we.94
|View full text |Cite
|
Sign up to set email alerts
|

Wind Resource Estimation—An Overview

Abstract: This article gives an overview of the different ways the wind resource at a site can be estimated. Eight separate ways have been identified. Each of these will be described in some detail, and advantages and disadvantages of each of them will be discussed. Copyright © 2003 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 15 publications
0
137
0
Order By: Relevance
“…where f is the Coriolis parameter and A = 1.8 and B = 4.5 are dimensionless parameters according to [27]. Neutral atmospheric conditions are assumed as no temperature observations are available for estimation of the atmospheric stability.…”
Section: Spatial Averaging and Post-processing Proceduresmentioning
confidence: 99%
“…where f is the Coriolis parameter and A = 1.8 and B = 4.5 are dimensionless parameters according to [27]. Neutral atmospheric conditions are assumed as no temperature observations are available for estimation of the atmospheric stability.…”
Section: Spatial Averaging and Post-processing Proceduresmentioning
confidence: 99%
“…Nowadays, wind maps and global databases have been developed for many regions around the world, such as NCEP/NCAR and ECMWF databases, containing wind speed, temperature and pressure at several heights around the world (Landberg et al, 2003). However, low resolution of some existing data (i.e.…”
Section: Measurements -Data Collectionmentioning
confidence: 99%
“…The idea is to correlate short term measurements at the target site with an overlapping long time series of the reference site using simple statistical models. According to Landberg et al (2003) climatological representativeness is obtained by having measurements for at least 5 but preferably 10 years.…”
Section: Forecasting Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that the lower mean speeds are linked to the higher surface roughness lengths z 0 prevalent in urban environments [2][3][4]. The manifestation of turbulence however, is less well understood.…”
Section: IImentioning
confidence: 99%